2018
DOI: 10.21059/buletinpeternak.v42i2.33522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four Essential Oils on Nutrients Digestibility of In Vitro Ruminal Fermentation

Abstract: This research was done to study the effect of four essential oils (EOs), as feed additives, on ruminal nutrient digestibility in order to find out candidate of rumen modifier. Those four EOs were destilated from Foeniculum vulgare (Mill), Pinus merkusii (Jungh. & de Vriese), Cymbopogon nardus (L.) Rendle and Melaleuca leucadendra (L.). Their effect on dry matter (DM), organic matter (OM), crude protein (CP) and crude fiber (CF) digestibility were studied using in vitro rumen fermentation technique according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Consistent with our result on the effect of the EOBs on the HC diet, [ 18 ] reported a decrease in DM digestibility when thymol was supplemented at 500 mg/L in a dual-flow continuous culture system. Several other studies (both in vivo and in vitro studies) have reported similar depression in DM digestibility with inclusion of EOs and their mixtures [ 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Consistent with our result on the effect of the EOBs on the HC diet, [ 18 ] reported a decrease in DM digestibility when thymol was supplemented at 500 mg/L in a dual-flow continuous culture system. Several other studies (both in vivo and in vitro studies) have reported similar depression in DM digestibility with inclusion of EOs and their mixtures [ 17 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 69%
“…The observed decrease in IVDDM in the present with the inclusion of EOBs was expected as lipids tend to reduce DM digestibility. The decline in digestibility with the inclusion of EOBs could also be associated with a reduction in protozoa population that help to engulf starch in the rumen [ 17 ]. A reduction in the protozoa population also has additional advantages as they are mainly responsible for CH 4 production.…”
Section: Discussionmentioning
confidence: 99%
“…This study's pH value is within the range of values necessary for optimal rumen microbial activity. In a previous study, an increased essential oil supplementation did not affect pH (Gunal et al 2013;Kurniawati et al 2018).…”
Section: Effect Of Citronella Oil Supplementation On Rumen Fluid Char...mentioning
confidence: 68%
“…Our study found that EO inclusion at 3 mg/day did not affect the apparent digestibility coefficients of DM, NDF, or ADF, aligning with results from Lin et al [ 32 ], Benchaar et al [ 33 ] and Meyer et al [ 29 ], who also reported no significant changes with various EO treatments. Nonetheless, studies such as those by Kurniawati et al [ 34 ] and Metwally [ 35 ] have shown that EOs can either decrease or enhance digestibility based on the EO type and dosage, underscoring the complexity and context-dependency of EO effects.…”
Section: Discussionmentioning
confidence: 99%